Opportunistic infections in acquired immune deficiency syndrome result from synergistic defects of both the natural and adaptive components of cellular immunity - Siegal, F P; Lopez, C; Fitzgerald, P A; Shah, K; Baron, P; Leiderman, I Z; Imperato, D; Landesman, S (The Journal of clinical investigation, 1986)
We evaluated the cellular immunity of 408 clinically stratified subjects at risk for acquired immune deficiency syndrome (AIDS), to define the role of interferon-alpha production deficits in the pathogenesis of opportunistic infections (OI). We followed 115 prospectively for up to 45 mo. Onset of OI was associated with, and predicted by, deficiency both of interferon-alpha generation in vitro, and of circulating Leu-3a+ cells. Interferon-alpha production is an index of the function of certain non-T, non-B, large granular lymphocytes (LGL) that are independent of T cell help. Leu-3a+ cell counts are a marker of T cell function. OI did not usually develop until both of these mutually independent immune functions were simultaneously critically depressed, leading to a synergistic interaction. These data suggest that the AIDS virus affects a subset of LGL, and that cytokine production by these cells is an important component of the host defense against intracellular pathogens that becomes crucial in the presence of severe T cell immunodeficiency.